Physical volcanology, sedimentology and geochemistry of the Mid-Cretaceous Chisana Formation, south-central Alaska: implications for models of Wrangellia composite terrane accretion - Manselle, Patrick (Kansas State University, 2019)
Currently, there are two main models for Mesozoic suturing of the Wrangellia composite terrane in the North American Cordillera. Studies from southeastern Alaska and British Columbia suggest that collision of the Wrangellia composite terrane with the North American craton occurred during the Middle Jurassic, and that early volcanism and sedimentation occurred in post-accretionary transtensional basins that were created by a strike-slip fault system. Another model suggests that accretion in eastern Alaska and the Yukon Territory occurred during the late Jurassic-early Cretaceous; associated volcanism was subduction-related and basin development evolved from an offshore Jurassic intraoceanic arc to a Cretaceous collisional arc setting. South-central Alaska, in the Nutzotin Mts. where the Chisana Formation crops out, is an ideal location for testing models for Wrangellia accretion because it is defined by two major collisional episodes: the Mesozoic collision of the Wrangellia composite terrane, and the ~30Ma to ongoing collision of the Yakutat terrane. The Chisana Formation consists of a succession of volcanic and sedimentary strata that conformably overlie late Jurassic‒early Cretaceous marine sedimentary strata of the Nutzotin Mt. Sequence. Geochronologic and geochemical data from upper Chisana lavas document ~121 to 117 Ma arc volcanism, however lavas from the lower parts of the Chisana Formation may be >121 Ma. New stratigraphic analysis indicates that the lavas are >2-km-thick at the Bonanza Creek type section. The lavas are overlain unconformably by fluvial strata of the Beaver Lake Formation, the age of which is uncertain but between 117 – 98 Ma. Our field evidence suggests the Chisana Formation at Bonanza Creek can be divided into a lower subaqueous unit, a middle transitional unit, and an upper subaerial unit. Lateral lithofacies changes between Bonanza Creek and Jacksina Creek show a northwestward transition from a primarily marine environment of deposition/emplacement at Bonanza Creek to an environment that was primarily subaerial, with minor, shallow marine influences present at Jacksina Creek. Chisana Formation lavas sampled at both locations range from calc-alkaline to tholeiitic basalts to basaltic andesites. Stratigraphically lower lavas are typically more andesitic and become more basaltic and tholeiitic up-section. Trace element geochemistry shows high field strength element (Ti, Nb, Y, Zr) depletions relative to large ion lithophile elements (Rb, K, Ba) as well as hydrous mineral assemblages with calc-alkaline to tholeiitic chemistries, both of which are consistent with an arc origin. Our data imply more significant subaerial eruptions and sedimentation from an oceanic arc constructed upon Wrangellia than previously recognized from this area of the Wrangellia composite terrane. When combined with data from other studies in the area, all results support of an east-dipping, subduction-related island arc model for the origin of the Gravina-Nutzotin belt.
Keywords: Alaska; Gravina Nutzotin Belt; Chisana Formation; Island Arc Accretion; Wrangellia Composite Terrane; Subduction